INVENTARISASI INSECTA PADA PAKU SARANG BURUNG (ASPLENIUM NIDUS) DI TAMAN WISATA ALAM DANAU SICIKEH-CIKEH KABUPATEN DAIRI SUMATERA UTARA - Husnarika Febriani; Nazipatul Marhani Hasibuan; Rahmadina Rahmadina (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2021)
Insects are the dominant group of organisms that have many benefits for survival and belong to one class of a large group of phylum arthropods that have a strong outer covering and grooves forming body segments. Insects can be found in all regions of the earth's surface, on land, sea and air. Bird's Nest Nails (Asplenium nidus) can grow in damp areas, under trees, alongside roads or rivers and also have enormous benefits as a habitat for several insects. Insect inventory research on Bird's Nest Nails (Asplenium nidus) aims to determine the types of insects on Bird's Nest Nails (Asplenium nidus) in the Sicikeh-cikeh Lake Nature Tourism Park. The study was conducted in October to December 2019 using the Yellow Pan Trap method. Sampling was carried out as a whole at a size of 20 m x 20 m. Based on the results of the study in all locations obtained 34 families consisting of 10 orders, namely Ichneumonidae Family, Culicidae, Carcinophoridae, Gryllidae, Cercopidae, Cynipidae, Sciaridae, Stratiomydae, Erebidae, Entomobryidae, Drosophilidae, Muscidae, Staphylinidae, Coccinellidae, Braconidae, Chrysomelidae, Syrphidae, Cecidomyiidae, Elateridae, Crabronidae, Formicidae, Chironomidae, Empididae, Noctuidae, Sarcophagidae, Scarabaeidae, Agromyzidae, Carabidae, Acrididae, Calliphoridae, Tephritidae, Vespidae, Corydalidae and Crambidae. Based on the results of data analysis obtained insect diversity index worth 2.25 (medium category), while the dominant insects found in the Culicidae Family of the Diptera Order with a total of 231 taxon.